Pendidikan Karakter Islami dalam Bingkai Pancasila dan Berbasis Digital - Muhammad Zainal Abidin (PEDAGOGIA : JURNAL KEGURUAN DAN PENDIDIKAN, 2024)
Character education is the main pillar in the development of superior human resources and integrity. In the context of a religious and pluralistic Indonesian nation, strengthening character through Islamic values that are aligned with Pancasila is a strategic need, especially in the digital era which is full of moral and social challenges. This research aims to analyse the integration model of Islamic character education in the frame of Pancasila through a digital approach in Islamic education units.This research uses a qualitative approach with an explorative case study type. Primary data sources were obtained from in-depth interviews with Islamic education teachers, principals, and students from three Islamic education institutions, namely MI Muhammadiyah Blora, and SMP 1 Blora and MAN 1 Blora. In addition, observation of the online learning process and analysis of supporting documents were conducted to strengthen data validity. The results showed that digital-based integration of Islamic and Pancasila character values has been implemented through various innovative approaches such as digital storytelling, project-based learning, and online platform collaboration. These strategies have proven effective in improving students' understanding and internalisation of character values in a contextualised manner. However, limited digital literacy among educators and lack of digital value content training are challenges in its implementation. This research recommends strengthening teachers' digital competence and developing a character curriculum that is systemically integrated with learning technology.